An extensive study on the Employee job satisfaction in SQUARE Pharmaceuticals Ltd (CHQ Branch) - Tasnim, Zarin (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.